A palaeoclimatic record from the Ledo-Paniselian Aquifer in Belgium: indications for groundwater recharge and flow in a periglacial environment - Walraevens, Kristine; Blaser, Petra C.; Aeschbach, Werner; Van Camp, Marc (Quaternary international, 2020)
Understanding the mechanisms of groundwater recharge and flow in periglacial environments remains enigmatic. Methane releases from melting permafrost in a warming world are a hot topic in contemporary climate research. Noble gas analyses have been proposed to study methane-driven degassing in lakes as well as in permafrost terrains. The Ledo-Paniselian aquifer is shown to provide an analogue for such processes, from the last period of global warming after the LGM. It is postulated that recharge from methane bubbling thermokarst lakes to groundwater took place, and can be recognized by a specific signature in the groundwater. The Ledo-Paniselian aquifer offers unique opportunities to study periglacial groundwater recharge during the LGM, as it was located in the permanent permafrost area to the south of the ice sheet at that time. It contains Holocene and Pleistocene groundwaters, which are separated by a recharge gap, referring to permafrost during the LGM. This is confirmed by noble gas temperature (NGT) data. In the samples immediately upstream of this gap, several potential indicators for the specific methanogenic recharge conditions from thawing permafrost are being put forward, based on noble gases, chemical and isotopic data. Immediately upstream of the age gap, groundwaters show strikingly deviating HCO3−, SO42−, δ13C, δ18O and δ2H compared to the regional trend, while their 14C model ages are too young, and NGTs seem too high. These samples are affected by degassing, which is not an artefact of sampling, and which, according to their radiogenic helium concentrations, occurred early on, during recharge or shortly thereafter. The origin of these samples could be explained by the conditions prevailing as the permafrost thawed, and groundwater recharge could resume. It is inferred that the degassed samples were infiltrated during or shortly after the LGM, when recharge from methane bubbling thermokarst lakes to groundwater took place, associated to the melting permafrost.